The importance of using local species in ecotoxicological studies: nematodes of Amazonian occurrence vs. Caenorhabditis elegans in the analysis of lethal and sublethal effects of aluminium - Baia, Erivaldo; Cardoso, Adauto Lima [UNESP]; de Carvalho, Leandro Machado; do Amarante, Cristine Bastos; Amado, Lílian Lund; Venekey, Virág (Springer Nature, 2025)
It is recognized that in bioassays, especially those conducted for ecotoxicological purposes, preference should be given to the use of species that are adapted to the physical-chemical conditions of the environment to be monitored. However, to establish the use of alternative species instead of the standardized ones, it is recommended to carry out tests to assess/compare their sensitivity to contaminants. This study assessed the lethal and sublethal effects (growth, fertility, and reproduction) of different aluminium concentrations, including environmentally relevant concentrations recorded in the Amazon, on two nematode species (C. tropicalis and C. briggsae) with Amazonian occurrence and C. elegans. The species’ responses to aluminium exposure were different. In tests to assess lethal effect, C. elegans was the most sensitive (LC50 = 3.32 ± 1.89 mg/L), while C. tropicalis was the least sensitive (LC50 = 6.98 ± 2.20 mg/L). The LC50 for C. briggsae could not be estimated due to the lack of a concentration-dependent response. On the other hand, when sublethal effects were assessed at low aluminium concentrations (environmentally relevant concentrations), C. tropicalis was the most sensitive with an inhibition rate in both reproduction and growth; C. elegans was the least sensitive, and C. briggsae showed an intermediate response. Therefore, C. tropicalis and C. elegans adopted opposite strategies in response to aluminium exposure. This study reinforces the use of local species in ecotoxicological tests and suggests the use of C. tropicalis as a test organism in future bioassays to evaluate the effects of contaminants, particularly in the tropical/Amazon region.
Keywords: Amazon; C. tropicalis; Ecotoxicology; Nematoda; Resident species; Tropical region